Granuloma Following Tracheostomy Closure: An Overlooked Cause of Chronic Cough - Athar Adnan Uppal, Huma Aslam, Azhar Farooq, Salman Ahmed Niaz Mangrio, Muhammad Zia, Hafiz Muhammad Waseem Yaseen, Muhammad Irfan Khan, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Aim was to determine the management of tracheal granuloma among patients of dry cough after tracheostomy. Methods: Total 24 patients of both genders were presented in this study. After obtaining informed written consent detailed demographics of enrolled cases were recorded. All the patients were underwent for CT scan. Lesion of granuloma was completely excised via bronchoscopy. Outcomes among all cases were assessed. Results: There were 16 (66.7%) males and 8 (33.3%) females among all cases. The patients mean age was 38.16 years. Among all, 12 (50%) had severity of dry cough, moderate cough was found in 8 (33.3%) cases and 4 (16.7%) cases had mild cough. After procedure we found effectiveness among 22 (91.7%) cases. Satisfaction rate was 20 (83.3%). Conclusion: We concluded in this study after tracheostomy tracheal granuloma can be treated completed by using bronchoscopy to obtained good results. Keywords: Tracheal granuloma, tracheostomy, outcomes, dry cough